Transcultural Insights into the Christian Conversion of British Gujarati Hindus - Reifsnider, Usha (Studies in world christianity, 2020)
This article uses primary sources gathered through ethnographic research amongst a group of British Gujarati Christian converts located in the Greater London area. As the researcher is a British Gujarati convert to Christianity, I am mindful of my position in the selection of the topic, the design of the research, and analysis of the data gathered. Autoethnography encourages an added dimension of access to data and subsequent analysis. This insider access has given voice to experiences of being "altern" or "other".